STTS : How to win in the business dating game. - Connolly, Sharon (STTS Success skills series, 2013)
The measure of your success will most probably not depend on what you know, but who you know! It has never been more important to develop great relationships and ensure that you are in the right place at the right time. When you become an effective networker, opportunities will continually knock at your door. But simply connecting is not enough, and opportunities rarely happen by luck or accident. Skilful networkers plan their networking for a greater return on investment. Confident networkers polish their small talk and conversation to become a charming, popular guest at any event. In her cle.